Procalcitonin Clearance, CD64, and HLA-DR as Predictors of Outcome in Febrile Neutropenic Children With Lymphoreticular Malignancies. Issue 6 (August 2020) - Gomber, Sunil; Banerjee, Anindya; Dewan, Pooja; Das, Shukla; Ansari, M. Ahmad; Rai, Gargi; Singh, Praveen
Abstract : Background: Febrile neutropenia (FN) is a dreaded complication of cancer chemotherapy. There has been a lot of improvement in supportive care in FN that has drastically reduced the infection-related mortality in these patients. The focus now is on reducing infection-related morbidity, healthcare costs and optimizing the quality of life of the child as well as their family during these episodes. In this study, biomarkers were studied as predictors of outcome so that outcome can be predicted earlier, and treatment modified accordingly. Objective: To measure procalcitonin levels (at baseline and day 3), procalcitonin clearance, neutrophil CD64 expression levels (at baseline) and monocyte HLA-DR expression levels (at baseline), and their correlation with outcome. Setting: Tertiary care hospital. Study Type: Cross-sectional observational study. Population/Participants: Sixty-five episodes of FN in children below 12 years with lymphoreticular malignancies. Children receiving antibacterial and/or antifungal treatment within the last 7 days were excluded from the study. Methods: The subjects recruited into the study had undergone complete clinical and laboratory evaluation as per hospital protocol. Procalcitonin (day 0 and 3), neutrophil CD64 expression, and monocytic HLA-DR expression levels were measured in these patients. Results: Sixty-five episodes of FN were studied in children with lymphoreticular malignancy. It was found that procalcitonin and HLA-DR are very good markers of outcome, whereas CD64 although a good marker, was inferior to procalcitonin and HLA-DR in predicting outcome. Procalcitonin clearance was found to be superior to single value of procalcitonin. Furthermore, procalcitonin on day 3 was found to be a better predictor of outcome compared with its baseline value. Also, it was found that procalcitonin and HLA-DR had a significant correlation with baseline C-reactive protein levels. Conclusions: On the basis of the findings of the study we suggest that serial monitoring of procalcitonin levels be used in febrile neutropenic children with cancer. Procalcitonin levels on day 3 alone can be offered in resource poor setting. The role of HLA-DR and CD64 also seems promising and needs to be further explored in larger multicentric studies.